2007
DOI: 10.1186/1477-7827-5-11
|View full text |Cite
|
Sign up to set email alerts
|

A study of the prostate, androgens and sexual activity of male rats

Abstract: Background: The prostate is a sexual gland that produces important substances for the potency of sperm to fertilize eggs within the female reproductive tract, and is under complex endocrine control. Taking advantage of the peculiar behavioral pattern of copulating male rats, we developed experimental paradigms to determine the influence of sexual behavior on the level of serum testosterone, prostate androgen receptors, and mRNA for androgen receptors in male rats displaying up to four consecutive ejaculations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 42 publications
2
16
0
4
Order By: Relevance
“…Some authors have reported the degradation of Fos triggered by certain hormones [37]. This is an important issue for our investigation because the execution of sexual behavior in rats produces a significant increase in the serum level of androgens [38], and the cerebellum is an important center for steroid action [39]. Thus, we hypothesize that the sexual stimulation of the male triggers the expression of Fos, and the execution of behavior produces the increase in androgen levels that activate the proteolytic process for Fos degradation.…”
Section: Discussionmentioning
confidence: 93%
“…Some authors have reported the degradation of Fos triggered by certain hormones [37]. This is an important issue for our investigation because the execution of sexual behavior in rats produces a significant increase in the serum level of androgens [38], and the cerebellum is an important center for steroid action [39]. Thus, we hypothesize that the sexual stimulation of the male triggers the expression of Fos, and the execution of behavior produces the increase in androgen levels that activate the proteolytic process for Fos degradation.…”
Section: Discussionmentioning
confidence: 93%
“…However, in the VP copulation plus exogenous testosterone results in fewer cases of dysplasia. The VP expresses different proportion of AR and AR-mRNA [47] and such heterogeneity may account for the different effects observed following exogenous testosterone with repetitive copulation [8]. Interestingly, the results of the present study showed that LPS resulted in more cases of dysplasia in the VP.…”
Section: Discussionmentioning
confidence: 48%
“…In addition to the sympathetic activation, copulatory behavior also involves the parasympathetic pathway and endocrine factors (i.e., testosterone, prolactin, corticosterone) [21,[32][33][34]. Previously, we showed that prolactin, estrogen, and hyperthyroidism stimulate D1 activity, whereas androgens inhibit it [17].…”
Section: Discussionmentioning
confidence: 96%